Water-based anticorrosive paint for rare earth permanent magnet motor and preparation method of water-based anticorrosive paint

By using specific composition base paint and top paint on rare earth permanent magnet motors, the problem of insufficient adhesion performance in the prior art is solved, high adhesion and corrosion resistance are achieved, and anti-corrosion effect is improved.

CN119708947APending Publication Date: 2025-03-28GUANGDONG HOSEN NEW MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411881246.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The application of existing water-based anticorrosion paint on rare earth permanent magnet motor magnetic sheets has failed to effectively improve the adhesion performance of the coating and affect the anticorrosion effect.

Method used

The top paint consists of polyoxypropylene glycol, polyether polyol, anionic carboxylic acid hydrophilic chain extender, non-reactive surfactant, isonitrile resin and deionized water, combined with zinc powder, tungsten powder, aluminum powder, phenolic resin, isopropanol, modified hydrogenated castor oil and dispersant, by improving the adhesion properties of the bottom paint and the corrosion resistance and wear resistance of the top paint.

Benefits of technology

It realizes rapid adhesion and high adhesion of anticorrosion paint, and improves the corrosion resistance and wear resistance of the surface of rare earth permanent magnet motors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708947A_ABST
    Figure CN119708947A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, and particularly discloses a rare earth permanent magnet motor water-based anticorrosive paint, which comprises a prime paint and a top paint, the prime paint is prepared from the following components: polypropylene oxide glycol, polyether polyol, an anionic carboxylic acid hydrophilic chain extender, a non-reactive surfactant, isocyanate and deionized water; the top-layer paint comprises the following components: zinc powder, tungsten powder, aluminum powder, phenolic resin, isopropanol, modified hydrogenated castor oil and a dispersing agent. The water-based anticorrosive paint for the rare earth permanent magnet motor has the advantages of high environmental adaptability, high adhesion speed and high adhesive force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of water-based anti-corrosion paints, and more specifically, to a rare earth permanent magnet motor water-based anti-corrosion paint and a preparation method thereof. Background Art

[0002] Rare earth permanent magnet devices, especially the magnetic sheets of new energy vehicle motors, have extremely high requirements for anti-corrosion performance due to their wide application in various environmental conditions. Rare earth permanent magnet materials such as NdFeB are prone to form electrochemical micro-batteries in humid environments due to their strong chemical activity, leading to corrosion and affecting their performance and service life. Therefore, the application of water-based anti-corrosion paint on magnetic sheets of new energy motors needs to comprehensively consider factors such as the environmental adaptability of the material, coating adhesion and uniformity, and construction technology to ensure the performance and reliability of the motor.

[0003] The Chinese invention patent with the publication number CN102936455B discloses a NdFeB rare earth permanent magnet surface anticorrosion coating and its preparation method. The NdFeB rare earth permanent magnet surface anticorrosion coating consists of a bottom coating and a top coating. The bottom coating has a thickness of 10 to 25 μm and a chemical composition of 55 to 65% of one or two of zinc and aluminum, 0 to 5% of one or more of metal nickel, chromium, molybdenum, neodymium, praseodymium, cobalt, and titanium, and 34 to 40% of neutral resin; the top coating has a thickness of 5 to 15 μm and a chemical composition of 55 to 65% of one or more of zinc, aluminum, titanium, molybdenum, nickel, cobalt, and chromium, and 35 to 45% of phenolic resin or acrylic resin. The preparation method is to pretreat the permanent magnet surface first, prepare the bottom coating by centrifugal leaching, and prepare the top coating by rolling spraying.

[0004] Since rare earth permanent magnet material is a substrate with a porous structure, it is difficult for the coating to adhere evenly. Therefore, the adhesion performance of the coating is crucial to the anti-corrosion effect. The above technical solution only improves the environmental adaptability of the coating and optimizes the construction process. It has the disadvantage of not further improving the adhesion performance of the coating. Summary of the invention

[0005] In order to solve the problem that the above-mentioned coating does not further improve the adhesion performance of the coating formed by the anti-corrosion paint, the present application provides a water-based anti-corrosion paint that simultaneously improves the environmental adaptability of the anti-corrosion paint and the adhesion performance of the coating.

[0006] In the first aspect, the present application provides a rare earth permanent magnet motor water-based anti-corrosion paint, which adopts the following technical solution:

[0007] A rare earth permanent magnet motor water-based anticorrosive paint comprises a base coat and a top coat; the base coat comprises the following components: polyoxypropylene glycol, polyether polyol, anionic carboxylic acid hydrophilic chain extender, non-reactive surfactant, isocyanate and deionized water; the top coat comprises the following components: zinc powder, tungsten powder, aluminum powder, phenolic resin, isopropanol, modified hydrogenated castor oil and a dispersant.

[0008] By adopting the above technical scheme, the bottom paint of the present application has the functions of fast adhesion and high adhesion, and the top paint has the functions of high corrosion resistance and wear resistance; in the bottom paint, since polyoxypropylene glycol has more ether bonds, the polyether polyol further extends the chain to form a long-chain polyurethane prepolymer, and the longer ether bond segment can rotate freely and fully contact with water, and more hydrogen bonds are formed between the ether bonds and water molecules, so that the water absorption of the bottom paint is enhanced and the viscosity is increased; the anionic carboxylic acid hydrophilic chain extender further reacts with the long-chain polyurethane prepolymer to carry out amino and carboxyl reactions, and vertically extends the long-chain polyether polyol to finally form a network structure material with high viscosity; and the non-reactive ionic surfactant further modifies the network structure material, further increases the ether bonds, thereby increasing the viscosity; the bottom paint finally formed is a network structure with strong viscosity; the bottom paint also has more ether bonds, hydroxyl groups and carboxyl groups, and more groups can be combined with different groups on the surface and pores of the rare earth permanent magnet material, so that the bottom paint can quickly and firmly adhere to the surface of the rare earth permanent magnet motor;

[0009] In the top coat of paint, the electrode potential of zinc and aluminum is relatively low, which can play a role of cathodic protection and hinder corrosive media such as H2O and O2 from reaching the substrate; tungsten powder has high strength and high wear resistance, which increases the overall strength and wear resistance of the top coat of paint. Phenolic resin and metal powder are mixed to prepare the top coat of paint, so that the top coat of paint has both the elasticity and wear resistance of the resin and the protective effect of the metal powder. The top coat of paint and the bottom coat of paint work synergistically, which increases the environmental adaptability of the anti-corrosion paint coating while increasing the adhesion speed and high adhesion of the anti-corrosion paint coating.

[0010] Preferably, the primer comprises the following raw materials in parts by weight: 25-45 parts of polyoxypropylene glycol, 2-5 parts of polyether polyol, 14-16 parts of anionic carboxylic acid hydrophilic chain extender, 2-10 parts of non-reactive surfactant, 5-8 parts of isocyanate and 40-60 parts of deionized water.

[0011] By adopting the above technical scheme, polyoxypropylene glycol has more ether bonds and is the key to the base coat, therefore, the content of polyoxypropylene glycol is high; polyether polyol has a capping effect, and a small amount can play a capping role; anionic carboxylic acid hydrophilic chain extender is used for longitudinal chain extension, and the content is relatively high; non-reactive surfactant is used to increase the specificity of the base coat, and the amount is appropriate; a small amount of isocyanate is used for capping.

[0012] Preferably, the top coating comprises the following raw materials in parts by weight: 20-30 parts of zinc powder, 0.5-1.5 parts of tungsten powder, 8-15 parts of aluminum powder, 30-35 parts of phenolic resin, 25-32 parts of isopropyl alcohol, 1-3 parts of modified hydrogenated castor oil and 3-5 parts of dispersant.

[0013] By adopting the above technical scheme, zinc powder mainly plays the role of cathodic protection in the top paint, so the content of zinc powder is the highest, and aluminum powder and zinc powder work synergistically to jointly improve the cathodic protection effect of the top paint; tungsten powder has high hardness and high melting point, is not corroded by air at room temperature, and has relatively stable chemical properties, so it can be used as an added metal in the top paint to enhance strength and wear resistance, but because tungsten metal is a rare metal, the added amount is not large; phenolic resin is a resin for mixing different metal powders, and the added amount is also large; modified hydrogenated sesame oil plays an anti-sedimentation role.

[0014] Preferably, the anionic carboxylic acid hydrophilic chain extender is 2,2-dimethylol propionic acid.

[0015] By adopting the above technical scheme, after polyoxypropylene glycol and polyether polyol form a long-chain polyurethane prepolymer, the amino group in the long-chain polyurethane prepolymer and the carboxyl group in 2,2-dihydroxymethylpropionic acid generate carboxylates with good hydrophilicity, which plays a good role in the hydrophilicity and stability of the primer. With the increase of carboxylates, the hydrophilicity and swelling properties of the emulsion increase, the molecular chains are entangled with each other, and the interfacial tension between water molecules is reduced, thereby obtaining a small-particle-size and stable emulsion-like primer.

[0016] Preferably, the non-reactive surfactant is a perfluorooctyl polyether surfactant.

[0017] By adopting the above technical scheme, due to the extremely low surface tension of the perfluorooctyl polyether surfactant, after the perfluorooctyl polyether surfactant is added to the primer, the primer has better wettability on the surface of the permanent magnet motor, which helps to evenly distribute the primer on the surface of the permanent magnet motor, reduce surface defects such as orange peel, wrinkling, and edge shrinkage of the primer during the coating process, and obtain a smoother and more uniform primer surface.

[0018] Preferably, the polyether polyol is polytetramethylene glycol.

[0019] By adopting the above technical scheme, polytetrahydrofuran diol contains more ether bonds, which can not only form hydrogen bonds with water molecules, but also has excellent low temperature resistance, oil resistance, wear resistance and mildew resistance. The primer obtained by chain extension with polytetrahydrofuran diol can still maintain strong water absorption and high viscosity at low temperature and in a humid environment, and can quickly and firmly adhere to the surface of the rare earth permanent magnet motor.

[0020] Preferably, the thickness of the bottom layer of paint is 5-8 μm; the thickness of the top layer of paint is 16-20 μm.

[0021] By adopting the above technical solution, the thickness of the base paint is 5-8μm. The appropriate base paint thickness not only helps the base paint to spread quickly on the surface of the rare earth permanent magnet motor, but also has better spreading uniformity and smoothness. The thickness of the top paint is 16-20μm. The appropriate top paint thickness not only helps the top paint to adhere firmly to the base paint, but also enables the top paint to have high strength and high wear resistance, thereby protecting the surface of the rare earth permanent magnet motor.

[0022] In a second aspect, the present application provides a method for preparing a water-based anti-corrosion paint for a rare earth permanent magnet motor, using the following technical solution:

[0023] A method for preparing a water-based anticorrosive paint for a rare earth permanent magnet motor, the method comprising the following steps:

[0024] Step 1: reacting polyoxypropylene glycol with isocyanate to form a polyurethane prepolymer;

[0025] Step 2: adding polyether polyol to the prepolymer to perform chain extension to obtain a long-chain polyurethane prepolymer;

[0026] Step 3: The long-chain polyurethane prepolymer reacts with isocyanate to form a polyurethane polyol;

[0027] Step 4: reacting the polyurethane polyol with an anionic carboxylic acid hydrophilic chain extender to form a carboxyl polyurethane containing a polyurethane network structure;

[0028] Step 5: reacting the carboxyl polyurethane containing the polyurethane network structure with a perfluorooctyl polyether surfactant to obtain a polyurethane with specific functions;

[0029] Step 6: Add deionized water to disperse and emulsify the specific functional polyurethane under high-speed stirring to form a base coat.

[0030] By adopting the above technical scheme, after the polyurethane prepolymer is prepared in step 1, polyether polyol is added in step 2 to extend the chain to obtain a long-chain polyurethane prepolymer, the isocyanate in step 3 is a capping agent, which combines with the long-chain polyurethane prepolymer to prevent the long-chain polyurethane prepolymer from endlessly extending to obtain a polyurethane polyol; in step 4, the polyurethane polyol is reacted with an anionic carboxylic acid hydrophilic chain extender to vertically extend the long chain to obtain a carboxyl polyurethane with a network structure; in step 5, the carboxyl polyurethane with a network structure is reacted with a perfluorooctyl polyether surfactant to form a polyurethane with a relatively large viscosity and a specific function; and in step 6, it is mixed with deionized water for dispersion and emulsification, and the emulsion particles become fine, so that the uniformity of the prepared base paint is higher.

[0031] Preferably, the primer preparation method comprises the following steps:

[0032] Step 1: reacting polyoxypropylene glycol with isocyanate at 80° C. for 2 hours to form a polyurethane prepolymer;

[0033] Step 2: adding polyether polyol to the prepolymer, reacting at 70° C. for 1 hour, and performing chain extension to obtain a long-chain polyurethane prepolymer;

[0034] Step 3: The long-chain polyurethane prepolymer is reacted with isocyanate at 80° C. for 1 hour to form a polyurethane polyol;

[0035] Step 4: reacting the polyurethane polyol with an anionic carboxylic acid hydrophilic chain extender at 90° C. for 2.5 hours to form a carboxyl polyurethane containing a polyurethane network structure;

[0036] Step 5: reacting the carboxyl polyurethane containing the polyurethane network structure with a perfluorooctyl polyether surfactant to obtain a polyurethane product having specific functions;

[0037] Step 6: Add deionized water to the specific functional polyurethane under high-speed stirring for dispersion and emulsification for 5 minutes, and then stir at a low speed for 0.5 to 1 hour to form a polyurethane emulsion.

[0038] By adopting the above technical scheme, step 1 is reacted at 80°C for 2 hours, which is conducive to the rapid polymerization of polyoxypropylene glycol and isocyanate-terminated to obtain a polyurethane prepolymer with more ether bonds; step 2 is a chain extension step, which is reacted at 70°C for 1 hour, which can meet the chain extension requirements of the present application; step 3 is a chain termination step, which is reacted at 80°C for 1 hour to form a polyurethane polyol with suitable polymerization degree and winding degree; step 4 is a longitudinal chain extension of further reaction of anionic carboxylic acid hydrophilic chain extender and polyurethane polyol, so it needs to be completed at a higher temperature and for a long time, so this step is reacted at 90°C for 2.5 hours; step 6 is stirred step by step to obtain a small-particle-size and stable emulsion-like primer.

[0039] Preferably, the top coating preparation method comprises the following steps:

[0040] Step a: adding zinc powder, tungsten powder, and aluminum powder into isopropanol and stirring to obtain a metal slurry;

[0041] Step b: Mix and stir the metal powder slurry, phenolic resin, hydrogenated castor oil and dispersant to obtain a base coat.

[0042] By adopting the above technical solution, in step a, zinc powder, tungsten powder and aluminum powder are all metal powders. Compared with other substances, the density of metal powder itself is not much different. Therefore, the three are mixed with isopropyl alcohol and can be mixed evenly to form a metal powder slurry with high uniformity; in step b, they are further mixed with other substances to obtain a top coating with good performance and uniformity.

[0043] In summary, this application has the following beneficial effects:

[0044] 1. The primer of the present application has more ether bonds, hydroxyl groups and carboxyl groups, and more groups can combine with different groups on the surface and pores of the rare earth permanent magnet material, so that the primer can adhere to the surface of the rare earth permanent magnet motor quickly and firmly;

[0045] 2. In the top coating of the present application, the electrode potential of zinc and aluminum is relatively low, which can play a role of cathode protection; tungsten powder has high strength and high wear resistance, and phenolic resin and metal powder are mixed to prepare the top coating, so that the top coating has both the elasticity and wear resistance of the resin;

[0046] 3. The polyether polyol of the present application is used to extend the chain of the polyurethane prepolymer to obtain a long-chain polyurethane prepolymer, which is then terminated with isocyanate to obtain a polyurethane polyol; the polyurethane polyol is reacted with an anionic carboxylic acid hydrophilic chain extender to obtain a carboxyl polyurethane having a network structure; the carboxyl polyurethane having a network structure is reacted with a perfluorooctyl polyether surfactant to form a specific functional polyurethane with a relatively high viscosity; and then dispersion and emulsification are performed to obtain a higher uniformity of the prepared base coat. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 The purpose is to show the infrared spectrum of the base coat of Example 3 detected by a Thermo Nicolet is5 Fourier transform infrared spectrometer. DETAILED DESCRIPTION

[0048] The raw materials of the examples and comparative examples of the present application can all be purchased commercially.

[0049] Polyoxypropylene glycol, model, PPG-2000; isocyanate, AR; polytetrahydrofuran diol, average molecular weight 1000; 2,2-dihydroxymethyl propionic acid, purity 98%; 2,2-dihydroxymethyl butyric acid, purity 98%; Fluorolink D10-H, CAS number, 107852-51-7; Fomblin Z-DOL, CAS number, 107852-50-6; zinc powder, tungsten powder, aluminum powder, particle size, 5-10 microns; isopropyl alcohol, AR; phenolic resin, specification, 701#; hydrogenated sesame oil, CAS number, 8001-78-3;

[0050] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0051] Example

[0052] Example 1

[0053] A method for preparing a rare earth permanent magnet motor water-based anti-corrosion paint, the method comprising the following steps:

[0054] The bottom paint preparation method comprises the following steps:

[0055] Step 1: 25 g of polyoxypropylene glycol was reacted with 2 g of isocyanate at a stirring speed of 800 rpm and at 80° C. for 2 hours to form a polyurethane prepolymer;

[0056] Step 2: Add 5 g of polytetrahydrofuran diol to the polyurethane prepolymer, continue stirring at a speed of 800 rpm, react at 70° C. for 1 hour, perform chain extension, and obtain a long-chain polyurethane prepolymer;

[0057] Step 3: The long-chain polyurethane prepolymer reacts with 3 g of isocyanate, stirring at 300 rpm and reacting at 80° C. for 1 hour to form a polyurethane polyol;

[0058] Step 4: reacting the synthesized polyurethane polyol with 14 g of 2,2-dimethylol propionic acid, stirring at a speed of 300 rpm, and reacting at 90° C. for 2.5 hours to form a carboxyl polyurethane containing a polyurethane network structure;

[0059] Step 5: The carboxyl polyurethane containing the polyurethane network structure reacts with 10 g of perfluorooctyl polyether surfactant Fluorolink D10-H, stirring at a speed of 200 rpm and reacting at 70° C. for 1 hour to obtain a polyurethane product with specific functions;

[0060] Step 6: Add 60 g of deionized water to the polyurethane product with specific functions under high-speed stirring, disperse and emulsify at a speed of 500 rpm for 5 minutes, and then slowly mature and stir at a speed of 100 rpm for 0.5 hours to form a polyurethane emulsion.

[0061] The top coating preparation method comprises the following steps:

[0062] Step a: Add 20 g zinc powder, 1.5 g tungsten powder, and 8 g aluminum powder into 25 g isopropanol, and stir at 300 rpm for 30 min at room temperature to obtain a metal slurry;

[0063] Step b: Stir metal slurry, 35 g of phenolic resin, 3 g of hydrogenated castor oil and 3 g of dispersant PPG200 at 300 rpm for 30 min at room temperature to obtain a base coat.

[0064] Painting steps:

[0065] The rare earth permanent magnet motor sample was ultrasonically treated in 10% hydrochloric acid for 10 minutes, and rinsed and dried with high-purity water. Then, a centrifugal immersion and spinning machine was used to evenly apply the bottom paint to the surface of the rare earth permanent magnet after ultrasonication. The coating viscosity was 32s, the centrifugal immersion and spinning frequency was 35r / min, the immersion and spinning time was 10s, the curing heating temperature after immersion and spinning was 280°C, and the curing time was 30min, forming a bottom coating with a thickness of 5μm; then an automatic roller spraying machine was used to spray the top layer of paint on the bottom layer of paint. The coating viscosity was 20s, the spraying pressure was 0.8Mpa, the spraying distance was 100mm, the spraying amount was 20ml / min, the spraying time was 5min, the roller speed was 30r / min, the permanent magnet after roller spraying was cured and heated to 300°C, and the curing time was 30min, forming a top coating with a thickness of 16μm.

[0066] Example 2

[0067] A method for preparing a rare earth permanent magnet motor water-based anti-corrosion paint, the method comprising the following steps:

[0068] The bottom paint preparation method comprises the following steps:

[0069] Step 1: 45 g of polyoxypropylene glycol was reacted with 1 g of isocyanate at a stirring speed of 800 rpm and a temperature of 80° C. for 2 hours to form a polyurethane prepolymer;

[0070] Step 2: Add 2 g of polytetrahydrofuran diol to the polyurethane prepolymer, continue stirring at a speed of 800 rpm, react at 70° C. for 1 hour, perform chain extension, and obtain a long-chain polyurethane prepolymer;

[0071] Step 3: reacting the long-chain polyurethane prepolymer with 1 g of isocyanate, stirring at 300 rpm, and reacting at 80° C. for 1 hour to form a polyurethane polyol;

[0072] Step 4: reacting the synthesized polyurethane polyol with 16 g of 2,2-dimethylol propionic acid, stirring at a speed of 300 rpm, and reacting at 90° C. for 2.5 hours to form a carboxyl polyurethane containing a polyurethane network structure;

[0073] Step 5: The carboxyl polyurethane containing the polyurethane network structure reacts with 2 g of perfluorooctyl polyether surfactant Fluorolink D10-H, stirring at a speed of 200 rpm and reacting at 70° C. for 1 hour to obtain a polyurethane product with specific functions;

[0074] Step 6: Add 40 g of deionized water to the polyurethane product with specific functions under high-speed stirring, disperse and emulsify at a speed of 500 rpm for 5 minutes, and then slowly mature and stir at a speed of 100 rpm for 1 hour to form a polyurethane emulsion.

[0075] The top coating preparation method comprises the following steps:

[0076] Step a: 30 g of zinc powder, 0.5 g of tungsten powder, and 15 g of aluminum powder were added to 32 g of isopropanol, and stirred at 300 rpm for 30 min at room temperature to obtain a metal slurry;

[0077] Step b: Stir metal slurry, 30 g phenolic resin, 1 g hydrogenated castor oil and 5 g dispersant PPG200 at 300 rpm for 30 min at room temperature to obtain a base coat.

[0078] Painting steps:

[0079] The rare earth permanent magnet motor sample was ultrasonically treated in 10% hydrochloric acid for 10 minutes, and rinsed and dried with high-purity water. Then, a centrifugal immersion and spinning machine was used to evenly apply the bottom paint to the surface of the rare earth permanent magnet after ultrasonication. The coating viscosity was 32s, the centrifugal immersion and spinning frequency was 35r / min, the immersion and spinning time was 15s, the curing heating temperature after immersion and spinning was 280°C, and the curing time was 30min, forming a bottom coating with a thickness of 8μm; then an automatic roller spraying machine was used to spray the top paint on the bottom paint. The coating viscosity was 20s, the spraying pressure was 0.8Mpa, the spraying distance was 100mm, the spraying amount was 20ml / min, the spraying time was 6.5min, the roller speed was 30r / min, the permanent magnet after roller spraying was cured and heated to 300°C, and the curing time was 30min, forming a top coating with a thickness of 20μm.

[0080] Example 3

[0081] A method for preparing a rare earth permanent magnet motor water-based anti-corrosion paint, the method comprising the following steps:

[0082] The bottom paint preparation method comprises the following steps:

[0083] Step 1: 35 g of polyoxypropylene glycol was reacted with 3 g of isocyanate at a stirring speed of 800 rpm and a temperature of 80° C. for 2 hours to form a polyurethane prepolymer;

[0084] Step 2: Add 3 g of polytetrahydrofuran diol to the polyurethane prepolymer, continue stirring at a speed of 800 rpm, react at 70° C. for 1 hour, perform chain extension, and obtain a long-chain polyurethane prepolymer;

[0085] Step 3: The long-chain polyurethane prepolymer reacts with 3 g of isocyanate, stirring at 300 rpm and reacting at 80° C. for 1 hour to form a polyurethane polyol;

[0086] Step 4: reacting the synthesized polyurethane polyol with 15 g of 2,2-dimethylol propionic acid, stirring at a speed of 300 rpm, and reacting at 90° C. for 2.5 hours to form a carboxyl polyurethane containing a polyurethane network structure;

[0087] Step 5: The carboxyl polyurethane containing the polyurethane network structure reacts with 6 g of perfluorooctyl polyether surfactant Fluorolink D10-H, stirring at a speed of 200 rpm and reacting at 70° C. for 1 hour to obtain a polyurethane product with specific functions;

[0088] Step 6: Add 50 g of deionized water to the polyurethane product with specific functions under high-speed stirring, disperse and emulsify at a speed of 500 rpm for 5 minutes, and then slowly mature and stir at a speed of 100 rpm for 1 hour to form a polyurethane emulsion.

[0089] The top coating preparation method comprises the following steps:

[0090] Step a: Add 25 g zinc powder, 1 g tungsten powder, and 11 g aluminum powder into 28 g isopropanol, and stir at 300 rpm for 30 min at room temperature to obtain a metal slurry;

[0091] Step b: Stir metal slurry, 32 g of phenolic resin, 2 g of hydrogenated castor oil and 4 g of dispersant PPG200 at 300 rpm for 30 min at room temperature to obtain a base coat.

[0092] Painting steps:

[0093] The rare earth permanent magnet motor sample was ultrasonically treated in 10% hydrochloric acid for 10 minutes, and rinsed and dried with high-purity water. Then, a centrifugal immersion and spinning machine was used to evenly apply the bottom paint to the surface of the rare earth permanent magnet after ultrasonication. The coating viscosity was 32s, the centrifugal immersion and spinning frequency was 35r / min, the immersion and spinning time was 12s, the curing heating temperature after immersion and spinning was 280°C, and the curing time was 30min, forming a bottom coating with a thickness of 6μm; then an automatic roller spraying machine was used to spray the top layer of paint on the bottom layer of paint. The coating viscosity was 20s, the spraying pressure was 0.8Mpa, the spraying distance was 100mm, the spraying amount was 20ml / min, the spraying time was 6min, the roller speed was 30r / min, the permanent magnet after roller spraying was cured and heated to 300°C, and the curing time was 30min, forming a top coating with a thickness of 18μm.

[0094] Example 4

[0095] The difference from Example 3 is that the 2,2-dihydroxymethylpropionic acid in step 4 of preparing the basecoat in Example 3 is replaced by an equal weight of 2,2-dihydroxymethylbutyric acid.

[0096] Example 5

[0097] The difference from Example 3 is that the perfluorooctyl polyether surfactant Fluorolink D10-H in step 5 of preparing the primer in Example 3 is replaced by an equal weight of perfluorooctyl polyether surfactant Fomblin Z-DOL.

[0098] Example 6

[0099] The difference from Example 3 is that the polytetrahydrofuran diol in the primer preparation step 2 of Example 3 is replaced with polyethylene glycol of equal weight.

[0100] Example 7

[0101] The difference from Example 3 is that the painting steps are different, and the specific steps are as follows:

[0102] The rare earth permanent magnet motor sample was ultrasonicated in 10% hydrochloric acid for 10 minutes, and rinsed and dried with high-purity water. Then, a centrifugal immersion and spinning machine was used to evenly apply the bottom paint to the surface of the rare earth permanent magnet after ultrasonication. The coating viscosity was 32s, the centrifugal immersion and spinning frequency was 35r / min, the immersion and spinning time was 6s, the curing heating temperature after immersion and spinning was 280°C, and the curing time was 30min, forming a bottom coating with a thickness of 3μm; then an automatic roller spraying machine was used to spray the top layer of paint on the bottom layer of paint. The coating viscosity was 20s, the spraying pressure was 0.8Mpa, the spraying distance was 100mm, the spraying amount was 20ml / min, the spraying time was 8min, the roller speed was 30r / min, the permanent magnet after roller spraying was cured and heated to 300°C, and the curing time was 30min, forming a top coating with a thickness of 25μm.

[0103] Example 8

[0104] The difference from Example 3 is that the reaction temperature of steps 1, 2, 3, 4 and 5 of preparing the primer is 80° C. and the reaction time is 2 hours.

[0105] Comparative Example

[0106] Comparative Example 1

[0107] The difference from Example 3 is that the polytetrahydrofuran diol in the primer preparation step 2 of Example 3 is not added.

[0108] Comparative Example 2

[0109] The difference from Example 3 is that the 2,2-dimethylolpropionic acid in step 4 of preparing the primer in Example 3 is not added.

[0110] Comparative Example 3

[0111] The difference from Example 3 is that the perfluorooctyl polyether surfactant Fluorolink D10-H in step 5 of preparing the primer in Example 3 is replaced by an equal weight of anionic surfactant dialkyl sulfosuccinate.

[0112] Comparative Example 4

[0113] The difference from Example 3 is that the tungsten powder in step a of preparing the top coating of Example 3 is not added.

[0114] Comparative Example 5

[0115] The difference from Example 3 is that the aluminum powder in step a of preparing the top coating of Example 3 is not added.

[0116] Comparative Example 6

[0117] The difference from Example 3 is that the hydrogenated castor oil in step b of preparing the top coating in Example 3 is replaced by an equal weight of polyolefin wax.

[0118] Performance testing

[0119] Detection Methods

[0120] Contact angle test

[0121] By using the static drop method, the base coat of Examples 1-8 and Comparative Examples 1-3 was placed on the surface of the rare earth permanent magnet motor sample, and the static contact angle of the base coat placed on the surface of the rare earth permanent magnet motor sample was measured using a JC200C1 static contact angle measuring instrument. Five points with equal spacing were taken on the surface of the rare earth permanent magnet motor sample for measurement, and the complete spreading time and the static contact angle after spreading were detected, and the average value was taken;

[0122] Adhesion test

[0123] According to the national standard GB / T9286-1998, the adhesion of the coating was measured by the cross-cutting-adhesive strip method. The samples of the embodiment and the comparative example were cross-cut in two vertical directions with a cross-cutting knife, and then the adhesive tape was pasted on the cut squares, and the adhesive tape was pulled out at a uniform speed. According to the shedding of the coating, the adhesion level of the coating was classified;

[0124] Pencil hardness test

[0125] The hardness of the rare earth permanent magnet motor water-based anti-corrosion paint coating reflects its ability to withstand mechanical forces such as scraping and scratching, and is one of the main indicators for judging mechanical strength. The samples of the embodiment and the comparative example were immersed in 5% NaCl water for 24 hours, and then the pencil hardness of the samples was tested using a BY pencil hardness tester according to the national standard GB / T6739-2006.

[0126] Table 1 Performance test results statistics

[0127]

[0128]

[0129] Combining the data of Examples 1, 2, and 3, it can be seen that the only difference between Examples 1, 2, and 3 is the different raw material composition ratios. The static contact angle of the primer of Example 3 on the surface of the rare earth permanent magnet motor sample is smaller than the static contact angle of the primer of Examples 1 and 2 on the surface of the rare earth permanent magnet motor sample, and the complete spreading time is short. Therefore, the raw material group of Example 3 is the optimal ratio for preparing the primer.

[0130] The difference between Examples 4, 5 and 6 and Example 3 is that the anionic carboxylic acid hydrophilic chain extender in Example 4 is 2,2-dihydroxymethylbutyric acid, and the perfluorooctyl polyether surfactant in Example 5 is Fomblin Z-DOL, the polyether polyol of Example 6 is polyethylene glycol. The results show that the static contact angle of the primer of Example 3 on the surface of the rare earth permanent magnet motor sample is smaller than the static contact angle of the primer of Examples 4, 5, and 6 on the surface of the rare earth permanent magnet motor sample, and the complete spreading time is short, but the complete spreading time of the primer of Examples 4, 5, and 6 on the surface of the rare earth permanent magnet motor sample is shorter than 20s, and the static contact angle is less than 10°; the adhesion and pencil hardness of the samples of Examples 3 and 4 are better than the adhesion and pencil hardness of the samples of Examples 5 and 6, and the adhesion of the samples of Examples 5 and 6 is also 0, and the pencil hardness reaches 4H; therefore, the anionic carboxylic acid hydrophilic chain extender of the present application can be selected from 2,2-dihydroxymethylbutyric acid or 2,2-dihydroxymethylpropionic acid; the perfluorooctyl polyether surfactant can be selected from Fomblin Z-DOL or Fluorolink D10-H; the polyether polyol can be selected from polyethylene glycol or polytetrahydrofuran diol.

[0131] The static contact angle of the base coat of Examples 7 and 8 on the surface of the rare earth permanent magnet motor sample is larger than that of the base coat of Example 3, and the complete spreading time is long, but the complete spreading time of the base coat of Examples 7 and 8 on the surface of the rare earth permanent magnet motor sample is shorter than 25s, and the static contact angle is less than 15°; the adhesion and pencil hardness of the sample of Example 3 are better than those of the samples of Examples 7 and 8, and the adhesion of the samples of Examples 7 and 8 is also 1, and the pencil hardness reaches 3H; therefore, the thickness of the base coat and the thickness of the top coat of the present application can exceed the optimal range specified in claim 7; and the temperature and time in the preparation steps of the base coat and the top coat are selected according to the temperature and time of Example 8, and a usable rare earth permanent magnet motor water-based anti-corrosion paint can be prepared.

[0132] In Comparative Examples 1 and 2, polyethylene glycol and 2,2-dihydroxymethylpropionic acid are not added respectively. The static contact angle of the primer of Comparative Examples 1 and 2 on the surface of the rare earth permanent magnet motor sample is larger than that of the primer of Example 3 on the surface of the rare earth permanent magnet motor sample, and the complete spreading time is long; the adhesion and pencil hardness of the sample of Example 3 are better than those of the samples of Comparative Examples 1 and 2, and the adhesion of the samples of Comparative Examples 1 and 2 is 2, and the pencil hardness is 1H; It is proved that polyethylene glycol and 2,2-dihydroxymethylpropionic acid are indispensable when preparing the primer.

[0133] In Comparative Example 3, the perfluorooctyl polyether surfactant Fluorolink D10-H is replaced with an equal weight of anionic surfactant dialkyl sulfosuccinate. The static contact angle of the primer of Comparative Example 3 on the surface of the rare earth permanent magnet motor sample is larger than the static contact angle of the primer of Example 3 on the surface of the rare earth permanent magnet motor sample, and the complete spreading time is long; the adhesion and pencil hardness of the sample of Example 3 are better than the adhesion and pencil hardness of the sample of Comparative Example 3, and the adhesion of the sample of Comparative Example 3 is 2, and the pencil hardness is H; It is proved that the anionic surfactant dialkyl sulfosuccinate cannot be used to prepare the primer of the present application.

[0134] In Comparative Examples 4 and 5, no tungsten powder or aluminum powder is added, respectively. The adhesion and pencil hardness of the sample of Example 3 are better than those of the samples of Comparative Examples 4 and 5. The adhesion of the samples of Comparative Examples 4 and 5 is 2, and the pencil hardness is H. This proves that tungsten powder and aluminum powder are indispensable when preparing the top coat.

[0135] In Comparative Example 6, hydrogenated castor oil is replaced with an equal weight of polyolefin wax. The adhesion and pencil hardness of the sample of Example 3 are better than those of the sample of Comparative Example 6. The adhesion of the sample of Comparative Example 6 is 2, and the pencil hardness is 1H; it is proved that polyolefin wax cannot be used to prepare the top coating of the present application.

[0136] Instructions attached Figure 1 In the infrared spectrum, 1102cm -1 The larger stretching vibration peak at 3317 cm -1 The stretching vibration peak at 2922 cm -1 With 1311cm -1 The stretching vibration peak at 2870 cm -1 With 1407cm -1 The stretching vibration peak at 1601 cm -1 The larger stretching vibration peak at 1311 cm -1 With 599cm-1 The stretching vibration peak at indicates the presence of -OH, proving that the primer prepared in the present application is indeed carried out according to the experimental steps of this scheme and the real results of this scheme are obtained.

[0137] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A rare earth permanent magnet motor water-based anti-corrosion paint, characterized in that: The invention comprises a base coat and a top coat; the base coat comprises the following components: polyoxypropylene glycol, polyether polyol, anionic carboxylic acid hydrophilic chain extender, non-reactive surfactant, isocyanate and deionized water; the top coat comprises the following components: zinc powder, tungsten powder, aluminum powder, phenolic resin, isopropyl alcohol, modified hydrogenated castor oil and dispersant.

2. A rare earth permanent magnet motor water-based anticorrosive paint according to claim 1, characterized in that: The primer comprises the following raw materials in parts by weight: 25-45 parts of polyoxypropylene glycol, 2-5 parts of polyether polyol, 14-16 parts of anionic carboxylic acid hydrophilic chain extender, 2-10 parts of non-reactive surfactant, 5-8 parts of isocyanate and 40-60 parts of deionized water.

3. A rare earth permanent magnet motor water-based anticorrosive paint according to claim 1, characterized in that: The top coating comprises the following raw materials in parts by weight: 20-30 parts of zinc powder, 0.5-1.5 parts of indium powder, 8-15 parts of aluminum powder, 30-35 parts of phenolic resin, 25-32 parts of isopropanol, 1-3 parts of modified hydrogenated castor oil and 3-5 parts of dispersant.

4. A rare earth permanent magnet motor water-based anticorrosive paint according to claim 1, characterized in that: The anionic carboxylic acid hydrophilic chain extender is 2,2-dimethylol propionic acid.

5. The rare earth permanent magnet motor water-based anticorrosive paint according to claim 1, characterized in that: The non-reactive surfactant is a perfluorooctyl polyether surfactant.

6. The rare earth permanent magnet motor water-based anticorrosive paint according to claim 1, characterized in that: The polyether polyol is polytetrahydrofuran diol.

7. The rare earth permanent magnet motor water-based anticorrosive paint according to claim 1, characterized in that: The thickness of the bottom paint is 5-8 μm; the thickness of the top paint is 16-20 μm.

8. A method for preparing a rare earth permanent magnet motor water-based anticorrosive paint according to any one of claims 1 to 7, wherein the base coat preparation method comprises the following steps: Step 1: reacting polyoxypropylene glycol with isocyanate to form a polyurethane prepolymer; Step 2: adding polyether polyol to the prepolymer to perform chain extension to obtain a long-chain polyurethane prepolymer; Step 3: The long-chain polyurethane prepolymer reacts with isocyanate to form a polyurethane polyol; Step 4: reacting the polyurethane polyol with an anionic carboxylic acid hydrophilic chain extender to form a carboxyl polyurethane containing a polyurethane network structure; Step 5: reacting the carboxyl polyurethane containing the polyurethane network structure with a perfluorooctyl polyether surfactant to obtain a polyurethane with specific functions; Step 6: Add deionized water to disperse and emulsify the specific functional polyurethane under high-speed stirring to form a base coat.

9. The method for preparing a rare earth permanent magnet motor water-based anticorrosive paint according to claim 8, wherein the method for preparing the primer comprises the following steps: Step 1: reacting polyoxypropylene glycol with isocyanate at 80° C. for 2 hours to form a polyurethane prepolymer; Step 2: adding polyether polyol to the prepolymer, reacting at 70° C. for 1 hour, and performing chain extension to obtain a long-chain polyurethane prepolymer; Step 3: The long-chain polyurethane prepolymer is reacted with isocyanate at 80° C. for 1 hour to form a polyurethane polyol; Step 4: reacting the polyurethane polyol with an anionic carboxylic acid hydrophilic chain extender at 90° C. for 2.5 hours to form a carboxyl polyurethane containing a polyurethane network structure; Step 5: reacting the carboxyl polyurethane containing the polyurethane network structure with a perfluorooctyl polyether surfactant to obtain a polyurethane product having specific functions; Step 6: Add deionized water to the specific functional polyurethane under high-speed stirring for dispersion and emulsification for 5 minutes, and then stir at a low speed for 0.5 to 1 hour to form a polyurethane emulsion.

10. The method for preparing a rare earth permanent magnet motor water-based anticorrosive paint according to claim 1, wherein the top coating preparation method comprises the following steps: Step a: adding zinc powder, tungsten powder, and aluminum powder into isopropanol and stirring to obtain a metal slurry; Step b: Mix and stir the metal powder slurry, phenolic resin, hydrogenated castor oil and dispersant to obtain a base coat.

Citation Information

Patent Citations

  • Neodymium iron boron rare earth permanent magnet surface anti-corrosion coating and preparation method thereof

    CN102936455B

  • Preparation method for waterborne polyurethane applied to elastic coating

    CN102492110A

  • Neodymium iron boron rare earth permanent magnet surface anti-corrosion coating and preparation method thereof

    CN102936455A

  • Rigid polyurethane foam material and preparation method thereof

    CN110105537A

  • Water-based antirust antistatic coating for chassis of sweeper

    CN112980267A